The mysterious edge of the heroic world - Konigsburg, E. L. (Aladdin Paperbacks, 2009)
Two new friends, Amedeo and William, find themselves working on a house sale for Amedeo's eccentric neighbor, Mrs. Zender. All of Mrs. Zender's keepsakes have their stories but the boys become interested in one that links a sketch and a painful secret from World War II.